Brand Affiliate sebagai Alternatif Membangun Brand Awareness - Trixie, Ivana; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Technological developments, especially in social media platforms such as TikTok, have changed the marketing paradigm by focusing on dynamic consumer interactions. This research explores the impact of TikTok in building brand awareness, especially with the emergence of the concept of